Heterozygous HNRNPU variants cause early onset epilepsy and severe intellectual disability - ELÇİOĞLU, HURİYE NURSEL (SPRINGER, 2017)
Pathogenic variants in genes encoding subunits of the spliceosome are the cause of several human diseases, such as neurodegenerative diseases. The RNA splicing process is facilitated by the spliceosome, a large RNA-protein complex consisting of small nuclear ribonucleoproteins (snRNPs), and many other proteins, such as heterogeneous nuclear ribonucleoproteins (hnRNPs). The HNRNPU gene (OMIM *602869) encodes the heterogeneous nuclear ribonucleoprotein U, which plays a crucial role in mammalian development. HNRNPU is expressed in the fetal brain and adult heart, kidney, liver, brain, and cerebellum. Microdeletions in the 1q44 region encompassing HNRNPU have been described in patients with intellectual disability (ID) and other clinical features, such as seizures, corpus callosum abnormalities (CCA), and microcephaly. Recently, pathogenic HNRNPU variants were identified in large ID and epileptic encephalopathy cohorts. In this study, we provide detailed clinical information of five novels and review two of the previously published individuals with (likely) pathogenic de novo variants in the HNRNPU gene including three non-sense and two missense variants, one small intragenic deletion, and one duplication. The phenotype in individuals with variants in HNRNPU is characterized by early onset seizures (6/7), severe ID (6/6), severe speech impairment (6/6), hypotonia (6/7), and central nervous system (CNS) (5/6), cardiac (4/6), and renal abnormalities (3/4). In this study, we broaden the clinical and mutational HNRNPU-associated spectrum, and demonstrate that heterozygous HNRNPU variants cause epilepsy, severe ID with striking speech impairment and variable CNS, cardiac, and renal anomalies.
Keywords: COPY-NUMBER VARIATION; DE-NOVO MUTATIONS; CORPUS-CALLOSUM; CANDIDATE GENES; CRITICAL REGION; DELETION; 1Q44; SEIZURES; ENCEPHALOPATHIES; ABNORMALITIES